2007
DOI: 10.1089/pho.2006.2030
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Laser Photobiomodulation (λ 830 nm) on Bone Tissue Around Dental Implants: A Raman Spectroscopy and Scanning Electronic Microscopy Study in Rabbits

Abstract: Objective: The aim of this study was to assess, through Raman spectroscopy, the incorporation of calcium hydroxyapatite (CHA; ~960 cm -1 ), and scanning electron microscopy (SEM), the bone quality on the healing bone around dental implants after laser photobiomodulation (830 nm). Background Data: Laser photobiomodulation has been successfully used to improve bone quality around dental implants, allowing early wearing of prostheses. Methods: Fourteen rabbits received a titanium implant on the tibia; eight of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…In addition to improved osseointegration, the authors also observed that the laser-treated group demonstrated enhanced healing of the surgical site and reduced swelling as compared to the control group. In another study, Lopes et al [13] assessed the bone quality and healing of rabbit tibial implants after laser treatments. Tibial implants were placed into fourteen rabbits; eight of the rabbits were laser treated, and the other six served as controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to improved osseointegration, the authors also observed that the laser-treated group demonstrated enhanced healing of the surgical site and reduced swelling as compared to the control group. In another study, Lopes et al [13] assessed the bone quality and healing of rabbit tibial implants after laser treatments. Tibial implants were placed into fourteen rabbits; eight of the rabbits were laser treated, and the other six served as controls.…”
Section: Resultsmentioning
confidence: 99%
“…The rabbits were sacrificed at on the 15th, 30th, and 45th day, and bone healing was evaluated using Raman sectroscopy and scanning electron microscopy. The authors found that there was significantly higher discrepancy in calcium hydroxyapatite deposition on the 30th and 45th day between the irradiated and control group ( P <0.001) [13]. The authors attributed these differences to the biostimulatory effects of laser treatments at the cellular level, as they increase adenosine triphosphate (ATP) production, osteoblast differentiation, and angiogenesis, potentially contributing towards improved bone mineral deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact molecular mechanism is not fully understood, significant clinical effects including analgesia, reduced inflammation and accelerated wound healing are well known [186,187]. A recent review and several previous research articles in animal models have highlighted the potential of PBM to improve dental implant stability by increasing osteocyte viability, osteoclast proliferation and improving bone repair and osseintegration [171,[188][189][190], although there exist limited randomized clinical trials in this area.…”
Section: Laser Therapy Photodynamic Therapy and Photobiomodulationmentioning
confidence: 99%
“…11), help speed the integration of the implant into the bone and improve the quality of the bone around the implant. A study 22 investigating the effect on infrared light on the loading time of dental implants found a significantly greater amount of mature bone, a bone with better distribution and organization after laser irradiation, when compared to the control group.…”
Section: Implantmentioning
confidence: 99%